Chemistry of Groundwater from the Taiyuan Formation Aquifer in Liuyi Coal Mine, Northern Anhui Province, China and Its Implications for Water Rock Interaction in Deep Seated Environment - Gui, H.R.; Sun, L.H. (Asian Journal of Chemistry, 2013)
Chemical compositions of groundwater from the Taiyuan formation aquifer in Liuyi coal mine, Northern Anhui Province, China have been measured for evaluating the hydro-chemical evolution in deep environments. The total dissolved solids values of groundwater range from 640 to 2567 mg/L and indicates moderate to highly mineralized and the ions are predominantly composed of (Na + K), Ca and SO4 with their average concentrations are 225, 117 and 508 mg/L, respectively. The groundwater samples are saturated with calcite and dolomite and undersaturated with gypsum with their average saturation indexes are 0.25, 0.18 and -1.29, respectively. The main minerals incorporated in the water rock interaction include halite, albite, K-feldspar, gypsum, pyrite, calcite and dolomite: Na and K are originated from the dissolution of halite, albite and K-feldspar, SO4 is from dissolution of gypsum and the dissolution and oxidation of pyrite, whereas Ca and Mg are originated from dissolution of calcite and dolomite.